Biographical sketch of 37 years of service at the Chair of Biochemistry, the Biochemistry and Nutrition Institute, and the Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos - Villavicencio-Núñez, Marino Marino (2007)
Universidad Nacional Mayor de San Marcos’ Emeritus Professor Dr. Marino Villavicencio Nuñez narrates in this article his personal experiences starting with early teaching steps as partial time Training chief and facts that traced his formation and national and international acknowledgement as one of the most outstanding researchers in biochemistry. Dr. Villavicencio is part and the manager of Biochemistry and Nutrition Research Center’s history. Nobody could relate better laboratories’ organization details, equipment, staff capacitation, and the highest level scientific production that lead our institution to be considered as an excellency biochemistry center in Latin America. Dr. Marino Villavicencio is an authentic Master and even though he ceased with 37 years of professional services he continues teaching us through his books on biochemistry, his up to date biochemistry digests and his wise counseling.